2013
DOI: 10.1371/journal.pone.0069256
|View full text |Cite
|
Sign up to set email alerts
|

Ixabepilone Administered Weekly or Every Three Weeks in HER2-Negative Metastatic Breast Cancer Patients; A Randomized Non-Comparative Phase II Trial

Abstract: To explore the activity and safety of two schedules of ixabepilone, as first line chemotherapy, in patients with metastatic breast cancer previously treated with adjuvant chemotherapy, a randomized non-comparative phase II study was conducted. From November 2008 until December 2010, 64 patients were treated with either ixabepilone 40 mg/m2 every 3 weeks (Group A, 32 patients) or ixabepilone 20 mg/m2 on days 1, 8 and 15 every 4 weeks (Group B, 32 patients). Overall response rate (the primary end point) was 47% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
5
0
2
Order By: Relevance
“…RR and median PFS or TTP for first-line monotherapies with chemotherapeutic drugs for metastatic breast cancer are presented in Table 3, including thrice weekly docetaxel, weekly gemcitabine, weekly intravenous vinorelbine, and thrice weekly ixabepilone. 2225 In general, these studies show that weekly eribulin monotherapy for non-HER2-overexpressing locally advanced or metastatic breast cancer, or in combination with trastuzumab for HER2-positive disease, lead to outcomes that are comparable with other tubulin-targeted agents and gemcitabine.…”
Section: Efficacy Of Eribulin Monotherapy In Locally Advanced Breast mentioning
confidence: 98%
“…RR and median PFS or TTP for first-line monotherapies with chemotherapeutic drugs for metastatic breast cancer are presented in Table 3, including thrice weekly docetaxel, weekly gemcitabine, weekly intravenous vinorelbine, and thrice weekly ixabepilone. 2225 In general, these studies show that weekly eribulin monotherapy for non-HER2-overexpressing locally advanced or metastatic breast cancer, or in combination with trastuzumab for HER2-positive disease, lead to outcomes that are comparable with other tubulin-targeted agents and gemcitabine.…”
Section: Efficacy Of Eribulin Monotherapy In Locally Advanced Breast mentioning
confidence: 98%
“…The results have been mixed. Fountzilas et al reported a randomized, non-comparative phase II trial in patients with mBC who had not previously received chemotherapy in the metastatic setting (42). In this trial, 32 participants received ixabepilone 40 mg/m 2 every 3 weeks and 32 participants received ixabepilone 20 mg/m 2 once weekly.…”
Section: Dose Modifications and Other Management Strategiesmentioning
confidence: 99%
“…Early phase studies with ixabepilone in mBC tested a higher dose (50 mg/m 2 IV every 3 weeks) and/or a shorter infusion period (1 hour), but poor tolerability led investigators to treat with ixabepilone 40 mg/m 2 IV over a 3-hour infusion in subsequent trials ( 26 ). To further test the efficacy of lower doses, two phase II trials evaluated more frequent administration of ixabepilone at lower than standard dosing ( 42 , 43 ). The results have been mixed.…”
Section: Overview Of Safety In Phase III Trialsmentioning
confidence: 99%
“…В исследованиях II и III фаз изучались 2 основных режима терапии иксабепилоном: 3-недельные введения в дозе 40 мг/м 2 и введения препарата в дозе 16-20 мг/м 2 еженедельно в течение 3 нед., далее перерыв 1 нед. [11][12][13]. Во всех данных исследованиях было продемонстрировано превосходство 3-недельного режима относительно ЧОО.…”
Section: иксабепилон при метастатическом раке молочной железыunclassified